Validation of Matching Nik, Npwp and Assistance In Filling Out Annual Tax Returns With Ibi Kosgoro Tax Volunteers For 2024 Term of Service - Prisila Damayanty; Zara Tania Rahmadi; Indra Setiawan; Kabul Wahyu Utomo; Tigha Anaku Putri (International Journal Of Community Service, 2024)
Matching of Population Identification Numbers (NIK) and Taxpayer Identification Numbers (NPWP), as well as assistance in filling out the Annual Tax Return (SPT). Validation of NIK and NPWP is a critical step in identifying and ensuring the validity of individual and company data in various administrative processes, especially those related to tax obligations. NIK validation involves matching a person's personal identity data with an official government database, while NPWP validation verifies the existence and validity of a company's tax identification number. These two processes support the accuracy of information used in various financial transactions and reporting. Apart from validation, assistance in filling out the Annual Tax Return is also important to ensure that the tax documents submitted comply with applicable tax regulations. This assistance can take the form of technical assistance in filling out SPT forms, consultation regarding income classification and processing tax deductions, as well as interpretation of the latest applicable regulations. Validation of NIK and NPWP as well as assistance in filling out the Annual SPT plays an important role in supporting administrative efficiency and tax compliance. By optimizing these processes, it is hoped that it can improve tax compliance, reduce the risk of administrative errors, and increase transparency and accountability in data management and financial reporting.